POLA PEMBERIAN ANTIBIOTIK DI PUSKESMAS SUKORAMBI, RAMBIPUJI PERIODE 17 OKTOBER-26 NOVEMBER 2011 - Kiswaluyo Kiswaluyo (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2011)
Introduction: The problem of bacterial resistance to antibiotics is a growing problem worldwide. Health center as a unit of local government health services are organized dental health services in the areas they use different types of antibiotics in improving public health. Purpose: discuss the administration of antibiotics in healthcenters. Results: The pattern of antibiotics has differences between health centers both in the amount and types of antibiotics. Conclusion: A wide range of variation of administration of antibiotics in health centers could occur because of differences in the availability, knowledge and creativity dentist dentist in the clinic